HCV co-infection is associated with metabolic abnormalities among HAART naïve HIV-infected persons (2017)
Objectives: To determine the metabolic abnormalities among Hepatitis C Virus (HCV) coinfected HAART naïve HIV infected persons within the adult ARV clinic of the University College Hospital/University of Ibadan, Ibadan, Nigeria Methods: This was a retrospective study involving the review of clinical records of newly recruited HIV-infected persons in the adult antiretroviral (ARV) clinic over a 12month period (January - December 2006). Baseline results for fasting plasma glucose (FPG) and fasting lipid profile were retrieved. Results: Out of the 1,260 HIV infected persons seen during the study period, HCV co-infection was found in 75 (6%) persons. The median values for total cholesterol, LDL-cholesterol and HDLcholesterol were lower in the HCV co-infected persons. HIV-HCV co–infection was associated with a 0.31 mmol/L depression in Total Cholesterol (TC). The median FPG concentration was significantly higher in HIV-HCV co–infected than HIV only infected persons (5.33mmol/L vs. 5.00mmol/L, p = 0.047). However, regression analysis showed there was no relationship between the HIV-HCV coinfected State and fasting glucose levels. Conclusion: HIV-HCV co-infection may be associated with a predictable decline in plasma cholesterol, but FPG may not be sufficient to demonstrate insulin resistance in these persons.